Acodos aereos en cacao (Theobroma cacao L.) CCN-51, mediante el uso de las hormonas sinteticas ANA (Acido naftalenacetico) y AIB (Acidoindolbutico) - Santander Coronel, Jefferson Enrique (2019)
The research objective was to obtain CCN-51 cocoa clones by aerial layers using synthetic hormones ANA (naphthalene acetic acid) and AIB (indole butyric acid); It was carried out in the Experimental Farm "La Represa", property of the State Technical University of Quevedo. A completely randomized design was used with a bifactorial arrangement (5 x 2), factor A (synthetic hormone doses ANA and AIB), and factor B (incidence of shade) in cocoa; obtaining 10 treatments with 6 repetitions, to determine the differences between the means of the treatments, the Tukey multiple range test will be used (P≤0.05). Variables of vegetative development (percentage of rooting, number, diameter, length of roots, root volume, diameter and length of callus, diameter of the branch) and an economic analysis at 60 days were evaluated. Within the results the dose that stood out was 3000 mg/kg of ANA + AIB with the use of substrate (sand, charcoal and peat) indicating a percentage of rooting of 95.47%, at the same time I present 2.38 mm, 7.29 cm and 1.32 mL for diameter, length and root volume respectively. In the variable of the diameter of the branch it did not show significance in the factors but in its interaction. The economic analysis showed that the T5 (3000mg/kg + SS), T6 (3000mg/kg + CS), T7 (3250mg/kg + SS) have a higher gross income are with a value of USD 8.80 each and in turn was the ones that obtained a higher R: B/C of 1.10.